THE RESULT OF USING INSTRUCTIONAL MODEL BY INTEGRATING INFORMATION PROCESSING THEORY AND SITUATED BASED LEARNING TO ENHANCE VIETNAMESE SPEAKING AND LISTENING COMPETENCIES FOR UNDERGRADUATE STUDENTS - Bich Thao, Tran Thi; Arunwong, Rekha; Oonyon, Nitikorn (Journal of MCU Nakhondhat, 2024)
The objective of this research was to 1) Study the progress of Vietnamese Listening and Speaking Communicative Competencies of Undergraduate Students by using an instructional model by integrating information process theory and situated based learning and 2) To compare Vietnamese Listening and Speaking Communicative Competencies of Undergraduate Students before and after using the instructional model by integrating information process theory and situated based learning. The sample group was 14 students in 3rd year in semester 1, academic year 2022, chosen by purposive sampling. The research tools were 1) The Vietnamese listening and speaking competency test for undergraduate students with the result of quality assessment at the highest level ( = 4.54, S.D. = .55) and the reliability index at .98 and 2) Vietnamese listening and speaking competency assessment form for undergraduate students indicated the validity index from .50 to 1.00 and the score of inter-rater reliability for scale at .97. Statistics employed for data analysis were the mean, standard deviation, and t-test and repeated measures through analysis of variance. The result found that students’ Vietnamese listening and speaking communicative competency development using thrice repeated measure revealed a higher tendency at a statistical significance of .05, and the samples’ learning achievement after using the instructional model was higher than before utilizing at the statistically significant of .05.